1996
DOI: 10.1021/bi950681o
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Contributing to the Formation of a β-Hairpin-like Structure in a Small Peptide

Abstract: A 12 amino acid peptide, model BB, was designed to adopt a beta-hairpin tertiary structure in water that might be stabilized by a variety of local, nonlocal, polar, and nonpolar interactions. The conformational properties of model BB with and without an intramolecular disulfide bond (BB-O and BB-R, respectively) were characterized by NMR and CD spectroscopy. The set of observed short- and medium-range nOes were consistent with the formation of stable beta-hairpin-like structures by both BB-R and BB-O. BB-O ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 32 publications
0
42
0
6
Order By: Relevance
“…The transposition of just two residues (DG3GD) causes the change from a type-I hairpin (below) to a diverging type-II turn. There is experimental evidence for a structure resembling this motif in a short peptide whose sequence matches this pattern (Sieber & Moe, 1996).…”
Section: Diverging Type-ii Beta-turnmentioning
confidence: 86%
See 1 more Smart Citation
“…The transposition of just two residues (DG3GD) causes the change from a type-I hairpin (below) to a diverging type-II turn. There is experimental evidence for a structure resembling this motif in a short peptide whose sequence matches this pattern (Sieber & Moe, 1996).…”
Section: Diverging Type-ii Beta-turnmentioning
confidence: 86%
“…Experimental evidence for this comes from NMR studies of isolated peptides. For the most part, peptides of 30 residues or less are found not to have a well-de®ned structure in water (Itzhaki et al, 1995;Yang et al, 1995), but many of the notable exceptions correspond to I-sites motifs, including the Schellman cap (Viguera & Serrano, 1995), the N-capping box , the serine b-hairpin (Blanco et al, 1994), the type-I b-hairpin (de Alba et al, 1996;Ilyina et al, 1994;Searle et al, 1995), and the diverging type-II turn (Sieber & Moe, 1996). In each case, a predominant solution structure was found that closely resembled the paradigm structure of the I-sites cluster that best matched its sequence.…”
Section: Folding Initiation Sitesmentioning
confidence: 99%
“…In the EF b-hairpin, backbone NH groups of residues Lys49, Ile51, Gln54, Gly57, Ala59 and Val65 do not show exchange, evidencing a single, stable conformation. Previous demonstrations that small peptides can form stable b-hairpins in aqueous solution (Blanco et al, 1994;Searle et al, 1995;Sieber & Moe, 1996) provide indirect evidence that the EF b-hairpin serves as a folding nucleus. The EF b-hairpin is one of four so-called folded hairpins which are a prominent feature of the protein S and bg-crystallin structures (Bagby et al, 1994a;Lapatto et al, 1991).…”
Section: Folding Of Protein S N-terminal Domain Via Multiple Nucleatimentioning
confidence: 99%
“…2. Hydrophobic residues, especially those with aromatic rings, are found to be stabilizing, with tryptophan being the best (the importance of cross-strand hydrophobic interactions has been hinted at in previous studies of β-hairpins [3,31,39,47]). The trend observed in Fig.…”
Section: Optimization Of Strand Sitesmentioning
confidence: 92%
“…This was done in the context of a 10-residue peptide with cysteine residues at position 1 and 10, threonine residues at position 2 and 9 (this amino acid tends to favor an extended backbone [35,51]), and a Glu-Gly-AsnLys sequence for residues 4-7 as it should have a moderate tendency to form a type II reverse turn [24]. Position 8 was initially chosen to be leucine, and naturally-occurring amino acids were substituted at [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]; ∆∆G estimated assuming additivity of data for trpzip4, 5 and 6. b Spaces separate strand from turn residues; substitutions in the gb1 C-terminal peptide are indicated bold and underlined. position 3 (the X3L8-series), with the aim of identifying the residue that most stabilized the β-hairpin structure [10].…”
Section: Optimization Of Strand Sitesmentioning
confidence: 99%